The people, press, and politics of Croatia - Malovic, Stjepan (Praeger, 2001)
This title examines the evolution of the press-government relationship in Croatia from the Tito era to the end of the 20th century. It is a story of three interacting players: the Croatian government, the compliant press and the largely quiescent public.